Contact decision and frequency decision: an econometric model of the demand for ambulatory services - Winfried Pohlmeier; Volker Ulrich (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1992)
The decision to contact a physician and the decision, how often to contact a physician, are based on different decision makers. We introduce a negative binominal distributed hurdle model that specifies the two stages of the decision process as different stochastic processes, and takes also care of the discrete nature of the data. Empirical results are based on a cross-section of the West-German Socioeconomic Panel. Specification tests reveal, that the two stages of the process have to be treated as distinct processes. Ignoring this distinction leads to serious misinterpretations.
Keywords: 330; Ärzte; Theorie; Deutschland